Research on Dual-Wavelength Single Polarizing Filter Based on Photonic Crystal Fiber - Boyao Li; Mingqin Li; Lu Peng; Guiyao Zhou; Zhiyun Hou; Changming Xia (IEEE Photonics Journal)
Dual-wavelength single polarizing filter has many important applications in the field of optical communication. Based on the principle of surface plasma resonance, a kind of dual-wavelength single polarizing filter with the broadband of low crosstalk was proposed in the paper by adopting good polarization characteristics of photonic crystal fiber. It could have single polarizing filtering in the dual-wavelength of 1310 and 1550 nm and the polarization direction of optical output is independent of the wavelength of incident light. The polarization direction of emergent light through filter can always keep the core mode in x-polarized direction (x-PCM) in a wide range of wavelength, which increases the difference of confinement loss of core mode in y-polarized direction (y-PCM) and x-PCM, and reduces mutual crosstalk. Meanwhile, the theoretical result also showed that the wavelength location and intensity of loss peak of polarizing mandrel are only affected by the air holes adjacent to fiber core and metal film and have little correlation with the structural parameters of other air holes, which ease the difficulty level of preparing filter based on photonic crystal fiber. Under certain structural parameters, the confinement loss of y-PCM could reach 265.04 dB/cm in 1310 nm and 230.5 dB/cm in 1550 nm. The half-width of confinement loss in the wavelength of 1310 nm is only 12 nm, while the loss of x-PCM is much smaller than that in y-PCM.